Comparison of Knowledge, Attitude, Motivation-to-Breastfeed Exclusively between Allied Health Students and Students of Other Fields at Universitas Padjadjaran - Astuti, Sri; Judistiani, Tina Dewi; Rahmiati, Lina; Susanti, Ari Indra (Majalah Kedokteran Bandung, 2016)
Comparison of Knowledge, Attitude, and Motivation-to-Breastfeed Exclusively between Allied Health Students and Students of Other Fields at Universitas PadjadjaranUniversity students are among future intellectuals who will play an important role in community education and empowerment, especially on the topic of exclusive breastfeeding, in which the coverage is low in Indonesia. This study aimed to compare students’ knowledge, attitude, and motivation-to-breastfeed exclusively between allied health studies (AHS), i.e medicine and midwifery,  and other fields studies (OFS), i.e. psychology, communication, literacy, and farming. Further information will be gained from exploring the correlation of knowledge-attitude, as well as attitude - motivation in both groups. A study was conducted among Indonesian female students in their final year of bachelor degree in October to November 2013. The subjects recruited were 196/340 female AHS and 300/633 female OFS. The remaining students were absent at data collection time. Validity and reliability of the questionnaires were satisfactory. Ethical clearance was obtained from the Committee on Health Research Ethics, Faculty of Medicine, Universitas Padjadjaran. The mean scores must be higher than the cut off points to pass. Student’s T test result showed a highly significant difference (AHS vs OFS group: 83.1 vs 71.1 for  knowledge, 91.3 vs 86.4 for attitude, and 88.3 vs 83.6 for  motivation-to-breastfeed exclusively,  p<0.001). It is revealed also that the correlation index between knowledge-attitude as well as attitude -  motivation-to- breastfeed exclusively were higher in AHS group, but some AHS students scored lower than the OFS students. Discussion on this topic is presented in this article. Corrective interventions are needed for students who scored low.  This study shows a satisfactory students’ scores of knowledge, attitude, motivation-to-breastfeed exclusively. The AHS group has a better performance and correlation index between  knowledge and attitude, attitude and  motivation-to-breastfeed exclusively. [MKB. 2016;48(3):176–80]Key words: Allied health students, attitude, knowledge, motivation-to-breastfeed exclusively, students of other fields Hubungan antara Pengetahuan dan Perilaku, serta Motivasi Menyusui pada Mahasiswi Fakultas Medis dan Non-medis di Universitas PadjadjaranMahasiswi universitas yang keberadaanya di antara para intelektual masa depan mempunyai peran penting dalam pendidikan dan pemberdayaan masyarakat, khususnya mengenai air susu ibu (ASI) eksklusif yang mempunyai cakupan rendah di Indonesia. Penelitian ini bertujuan membandingkan pengetahuan, sikap, dan motivasi untuk menyusui secara eksklusif antara beberapa studi kesehatan (AHS), yaitu kedokteran dan kebidanan, serta studi bidang lain (OFS), yaitu psikologi, komunikasi, sastra, dan pertanian. Informasi lebih lanjut akan mengeksplorasi hubungan pengetahuan, sikap, serta sikap-motivasi pada kedua kelompok. Penelitian ini dilakukan dari Oktober–November 2013. Sampel terdiri atas 196/340 perempuan AHS dan 300/633 OFS perempuan di Universitas Padjadjaran. Sampel yang tidak diambil adalah mahasiswi yang tidak hadir pada saat pengumpulan data. Validitas dan reliabilitas kuesioner yang memuaskan. Izin etik diperoleh dari Komite Etik Penelitian Kesehatan Fakultas Kedokteran Universitas Padjadjaran. Hasil nilai yang lebih tinggi mempunyai poin untuk lulus. Hasil uji-t mahasiswi menunjukkan perbedaan yang sangat signifikan (AHS vs kelompok OFS adalah 83,1 vs 71,1 untuk pengetahuan, 91,3 vs 86,4 sikap, dan 88,3 vs 83,6 motivasi untuk menyusui secara eksklusif, p<0,001). Indeks korelasi antara pengetahuan dan sikap serta sikap dengan motivasi untuk menyusui secara eksklusif lebih tinggi pada kelompok AHS, namun beberapa mahasiswi AHS mempunyai nilai lebih rendah daripada mahasiswi OFS. Hal tersebut dibahas dalam artikel, intervensi korektif yang diperlukan antara mahasiswi yang mendapat nilai rendah. Penelitian ini menunjukkan hasil yang memuaskan pada nilai mahasiswi tentang pengetahuan, sikap, dan motivasi untuk menyusui secara eksklusif. Kelompok AHS menunjukkan kinerja dan indeks korelasi yang lebih baik antara pengetahuan dan sikap, sikap dengan motivasi untuk menyusui secara eksklusif. [MKB. 2016;48(3):176–80]Kata kunci: Mahasiswi kesehatan, motivasi untuk menyusui secara eksklusif, mahasiswi non-kesehatan, sikap dan pengetahuan